Transitional (in)Justice and Enforcing the Peace on Palestine - Browne, Brendan Ciarán. author. (orcid)0000-0002-3568-7565 Link aut Link
XIII, 97 p. 1 illus.
Keywords: This book considers the growing interest in transitional justice practices that take place against the backdrop of ongoing settler-colonialism in Palestine. By critiquing the role of common top-down and bottom-up interventions, namely truth recovery and international criminal justice, the book argues that transitional justice acts as an extension of a deeply flawed peacebuilding process that has been so destructive in Palestine and has a deflating effect when it comes to advancing calls for meaningful decolonisation. A ‘radicalisation’ of transitional justice that takes place in settler-colonial contexts, one that prioritises conversations around meaningful decolonisation, is therefore required. The book will appeal to those with an interest in peacebuilding, conflict transformation and transitional justice. Dr Brendan Ciarán Browne is Assistant Professor Conflict Resolution & Reconciliation, Trinity College Dublin, Ireland and Fellow at the Trinity Centre for Resistance Studies.